COVID-19: the end of lockdown what next? - Castaldi, Silvana; Romano, Luisa; Pariani, Elena; Garbelli, Claudio; Biganzoli, Elia (Acta Biomedica Atenei Parmensis, 2020)
The Corona Virus 19 (COVID 19) epidemic is an infectious disease which was declared as a pandemic and hit all the Countries, all over the world, from the beginning of the year 2020. In Italy the epidemic is particular serious with 169.325 confirmed cases and 21.551 deaths on 20.04.2020. To stop the contagion on March 8 and up to May 3, the Italian Government decided a lockdown for all the Country, the authors suggest how to manage the reopening and restarting of all the activities avoiding a restart of the epidemic.